Ileocolic junction resection in dogs and cats: 18 cases. Issue 1 (1st January 2017) - Fernandez, Yordan; Seth, Mayank; Murgia, Daniela; Puig, Jordi
ABSTRACT: There is limited veterinary literature about dogs or cats with ileocolic junction resection and its long-term follow-up. To evaluate the long-term outcome in a cohort of dogs and cats that underwent resection of the ileocolic junction without extensive (≥50%) small or large bowel resection. Medical records of dogs and cats that had the ileocolic junction resected were reviewed. Follow-up information was obtained either by telephone interview or e-mail correspondence with the referring veterinary surgeons. Nine dogs and nine cats were included. The most common cause of ileocolic junction resection was intussusception in dogs (5/9) and neoplasia in cats (6/9). Two dogs with ileocolic junction lymphoma died postoperatively. Only 2 of 15 animals, for which long-term follow-up information was available, had soft stools. However, three dogs with suspected chronic enteropathy required long-term treatment with hypoallergenic diets alone or in combination with medical treatment to avoid the development of diarrhoea. Four of 6 cats with ileocolic junction neoplasia were euthanised as a consequence of progressive disease. Dogs and cats undergoing ileocolic junction resection and surviving the perioperative period may have a good long-term outcome with mild or absent clinical signs but long-term medical management may be required.